Exploring the effects of subsoiling tillage under various irrigation regimes on the evapotranspiration and crop water productivity of winter wheat using RZWQM2 - Shiyu Wei; Naikun Kuang; Fengli Jiao; Rui Zong; Quanqi Li (Agricultural Water Management, 2023)
Food security is an important pre-requisite for human well-being; however, water shortages and poor quality of arable land threaten food security in the North China Plain (NCP). Subsoiling and proper irrigation can improve soil structure and increase crop yield. This study investigated the effects of two tillage methods (rotary tillage at 15 cm depth, R15; subsoiling at 35 cm depth, S35) combined with three irrigation treatments (no irrigation during the winter wheat growing season, I0; 60 mm irrigation at the jointing stage, I1; 60 mm irrigation at both the jointing and heading stages, I2) on soil moisture dynamics, evapotranspiration, and winter wheat yield. The Root Zone Water Quality Model (RZWQM2) was adopted after calibration and validation base on a field experiment. The results showed that the normalized root mean square errors (calibration and test) between the actual and simulated values of soil water storage (SWS), evapotranspiration (ET), and yield were 7.45–10.87%, 3.80–7.21%, and 5.38–14.15%, respectively. Subsoiling improved winter wheat soil moisture conditions, yield, and crop water productivity (CWP), and irrigation during the winter wheat growing seasons increased crop yield (I2 > I1 > I0) and CWP (I1 > I2 > I0). The best yield treatment during the 2020–2022 winter wheat growing seasons was S35-I2. However, the CWP of S35-I1 was 2.67% higher than that of S35-I2. Tillage methods change the ET structure of winter wheat fields. Compared to rotary tillage, subsoiling reduced actual ET by 16.11% and increased actual transpiration by 10.44%. The results of this study indicate that subsoiling at a depth of 35 cm and 60 mm irrigation at the jointing stage could improve the CWP of winter wheat in the NCP.